x2 - 2(x - y);x = 6 and y = 2

Question

Asked 10/18/2013 9:25:06 AM

Updated 10/21/2013 12:26:24 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey

andrewpallarca|Points 26593|

reynaldo009|Points 292|

kielan1|Points 85|

Question

Asked 10/18/2013 9:25:06 AM

Updated 10/21/2013 12:26:24 AM

3 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey

Rating

0

when x = 6 and y = 2,

x2 - 2(x - y)

= 36 - 2(6-2)

= 36 - 8

= 28

x2 - 2(x - y)

= 36 - 2(6-2)

= 36 - 8

= 28

Added 10/21/2013 12:23:11 AM

0

-2[7x - 7 - 6(x + 1)] = 2x + 5

-2(7x - 7 - 6x - 6) = 2x + 5

-2(x - 13) = 2x + 5

-2x + 26 = 2x + 5

4x = 21

x = 21/4

-2(7x - 7 - 6x - 6) = 2x + 5

-2(x - 13) = 2x + 5

-2x + 26 = 2x + 5

4x = 21

x = 21/4

Added 10/21/2013 12:25:32 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [7/8/2014 11:37:21 AM]

0

27,087,740

questions answered

There are no comments.